2019
DOI: 10.2147/ott.s201799
|View full text |Cite
|
Sign up to set email alerts
|

<p>Progression of the role of CRYAB in signaling pathways and cancers</p>

Abstract: CRYAB is a member of the small heat shock protein family, first discovered in the lens of the eye, and involved in various diseases, such as eye and heart diseases and even cancers, for example, breast cancer, lung cancer, prostate cancer, and ovarian cancer. In addition, CRYAB proteins are involved in a variety of signaling pathways including apoptosis, inflammation, and oxidative stress. This review summarizes the recent progress concerning the role of CRYAB in signaling pathways and diseases. Therefore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 152 publications
0
65
0
1
Order By: Relevance
“…We used cell-type marker analysis to identify the most upregulated genes in these clusters and found that these clusters are likely driving the upregulation of iron accumulation and cell stress genes observed in the differential gene expression test described above. Gene expression analysis between conditions once again revealed an increase in iron accumulation genes (FTH1 and FTL (Iancu 1992;Vidal et al 2004)) and a cell stress gene (CRYAB (Ousman et al 2007;Zhang et al 2019)) ( Fig. 3c).…”
Section: Iron Accumulation and Cell Stress In Cte-specific Olsmentioning
confidence: 89%
See 1 more Smart Citation
“…We used cell-type marker analysis to identify the most upregulated genes in these clusters and found that these clusters are likely driving the upregulation of iron accumulation and cell stress genes observed in the differential gene expression test described above. Gene expression analysis between conditions once again revealed an increase in iron accumulation genes (FTH1 and FTL (Iancu 1992;Vidal et al 2004)) and a cell stress gene (CRYAB (Ousman et al 2007;Zhang et al 2019)) ( Fig. 3c).…”
Section: Iron Accumulation and Cell Stress In Cte-specific Olsmentioning
confidence: 89%
“…To further understand the gene expression changes that might be driving the observed OL differences in CTE, we tested for differential gene expression between conditions. The most differentially expressed genes between conditions included CRYAB (anti-apoptotic and neuroprotective factor (Zhang et al 2019;Ousman et al 2007;Schirmer et al 2019)) and FTH1 (iron accumulation (Iancu 1992;Vidal et al 2004;Schirmer et al 2019)) ( Fig. 2e).…”
Section: Global Depletion Of Ols In Cte White Mattermentioning
confidence: 97%
“…WGCNA is a powerful tool for analysing multiple genes in large-scale datasets. It has been extensively used to explore gene co-expression modules and hub genes as potential target biomarkers in many cancers (Foroughi et al, 2018;Chen et al, 2018;Giulietti et al, 2016;Liu et al, 2019;Wang et al, 2019a;Wang et al, 2019b;Xu et al, 2018;Zhai et al, 2019;Zhang et al, 2019a;Zhang et al, 2019b;Zhang et al, 2019c). In the current study, we applied WGCNA and systematically identified the turquoise module as the most significantly negatively associated (r = −0.2, P = 4e−04) with pathologic stage for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Another study (Ding et al, 2019) have also reported that the pseudopodium-enriched atypical kinase 1-PPP1R12B axis inhibits colorectal tumourigenesis and metastasis through the deactivation of the Grb2/PI3K/Akt pathway, which might provide a novel therapeutic strategy for CRC treatment. The hub gene CFD was identified and validated as a potential target gene in papillary thyroid cancer (Zhang et al, 2019a;Zhang et al, 2019b;Zhang et al, 2019c). CRYAB is a very important protein involved in a variety of signal transduction pathways, including apoptosis, inflammation and oxidative stress (Zhang et al, 2019a;Zhang et al, 2019b;Zhang et al, 2019c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation